RANCANG BANGUN ALAT CUCI TANGAN OTOMATIS PORTABLE DENGAN TEKNOLOGI MIKROKONTROLER ARDUINO UNO - Rizki Febriansyach; Dian Budhi Santoso; Ulinnuha Latifa (Electro Luceat, 2020)
Washing hands is an activity that is very important for health. Based on the 2018 Riskesdas data, 49.8% of the total population in Indonesia still has not implemented a clean lifestyle. Based on this, we need a media that can attract public interest in implementing a clean lifestyle. So that a portable automatic handwashing tool was made using Arduino technology as a microcontroller control and monitoring. This handwashing tool uses a solar panel with a capacity of 10Wp and a 12V / 5Ah battery, which is based on the results of tests that state that the solar panel and battery used are not optimal to be able to run the automatic handwashing system.